Gastrointestinal motility in patients with end‐stage renal disease on chronic hemodialysis. Issue 4 (22nd January 2019) - Broberg, Bo; Madsen, Jan L.; Fuglsang, Stefan; Holst, Jens J.; Christensen, Karl Bang; Rydahl, Casper; Idorn, Thomas; Feldt‐Rasmussen, Bo; Hornum, Mads
Abstract: Background: Previous studies indicated delayed gastric emptying in patients with end‐stage renal disease (ESRD) using indirect methods. The objective of the current study was to examine gastrointestinal motility using a direct method as well as the role of the incretin hormones and glucagon. Methods: Patients on chronic hemodialysis and with either normal glucose tolerance, impaired glucose tolerance or type 2 diabetes, and healthy control subjects (N = 8, respectively) were studied. Gastric emptying time was measured by repeated gamma camera imaging for 6 hours after intake of a radioactive labeled standardized mixed solid and liquid meal. Glucagon, glucagon‐like peptide‐1 (GLP‐1), and glucose‐dependent insulinotropic polypeptide (GIP) levels were measured. Key Results: Patients were age, gender and BMI matched with controls. We found significantly higher gastric retention at 15 minutes, prolonged gastric mean emptying time, and gastric half‐emptying time of the solid marker in all three groups of ESRD patients compared to controls. Significant differences in mean total area under the concentration curve (AUC) values across the four groups for GIP ( P  = 0.001), but not for GLP‐1 and glucagon. The ESRD group had significant higher total AUC of GIP and glucagon compared to controls ( P  < 0.001 and P  < 0.04) but not for GLP‐1 ( P  = 0.4). No difference in incremental AUC was found. Conclusions and Inferences: We found altered gastrointestinal motility in dialysis patients, with higher gastric retention and prolonged gastric emptying, and higher total AUC of GIP and glucagon independent of the presence of diabetes or prediabetes. Abstract : We found altered gastrointestinal motility in dialysis patients, with higher gastric retention and prolonged gastric emptying, and higher total AUC of GIP and glucagon hormones independent of the presence of diabetes or prediabetes.